1982
DOI: 10.1088/0031-9155/27/2/005
|View full text |Cite
|
Sign up to set email alerts
|

Use of the FBX dosemeter for the calibration of cobalt-60 and high-energy teletherapy machines

Abstract: The doses from the cobalt-60 teletherapy machines were measured using the FBX and secondary-standard dosemeters of Farmer-Baldwin type. The FBX dosemeter contained 0.20 mM ferrous ammonium sulphate, 5.0 mM benzoic acid and 0.20 mM xylenol orange in 0.05 N sulphuric acid. The values were compared with the values from a Fricke dosemeter and a graphite chamber used as primary standards. The values of the FBX, Fricke and graphite chambers agreed. There were, however wide differences among the different secondary-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 30 publications
3
20
1
Order By: Relevance
“…The correlation coefficient R 2 was 0.9996 which showed an excellent linear fit for the dose range of interest. The linear interval tested is consistent with the results cited in the literature [4,11] and is adequate for radiotherapy purposes. The radiation chemical yield G(Fe +3 ) value, which is a product of this slope and the molar extinction coefficient, ε, was evaluated and found to be 55.96 (± 0.40) × 10 −7 mol J −1 .…”
Section: Dose Responsesupporting
confidence: 87%
See 1 more Smart Citation
“…The correlation coefficient R 2 was 0.9996 which showed an excellent linear fit for the dose range of interest. The linear interval tested is consistent with the results cited in the literature [4,11] and is adequate for radiotherapy purposes. The radiation chemical yield G(Fe +3 ) value, which is a product of this slope and the molar extinction coefficient, ε, was evaluated and found to be 55.96 (± 0.40) × 10 −7 mol J −1 .…”
Section: Dose Responsesupporting
confidence: 87%
“…The FBX aqueous chemical dosimetry system that was developed for low level dose measurements by Gupta and co-workers [1][2][3] has found many applications in radiotherapy owing to its improved sensitivity at low doses as compared to Fricke system. It has been found useful for depth dose measurements, output calibration [4] quality assurance in external beam therapy [5], brachytherapy source calibration [6], in vivo dose measurements [7], and for measurement of virtual wedge profiles [8]. In this system absorbed doses are measured in terms of the oxidation yield of ferric ions produced by irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The study about dose response of benzoic Fricke gel was initiated using the composition reported originally by Gupta et al: 9 , 15 0.2 mM ferrous ammonium sulfate, 0.05 mM sulfuric acid, 0.2 mM Xylenol orange, 5 mM benzoic acid. The chemical composition of sensitive material was modified in the first instance, using suggestions provided in literature, mainly by Gupta et al 15 , 30 , 34 , 35 Also, suggestions by other authors were taken into account regarding the preparation process, 3 , 6 as well as cooling and storage procedures. (3,6,13) The formulation of benzoic Fricke gel is going to be used in the present study as the base for characterization of dosimetry performance of the μCT facility.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this work is to develop, characterize, and execute preliminary implementation of a dosimetric radiation detector with high enough sensitivity capable of performing reliable absorbed‐dose distribution measurements for low‐dose level, as required by radiological procedures 3 , 30 . The study begins with a pre‐established composition of FXG for the measurement of radiation dose levels typically used for therapeutic purposes (i.e., relative high doses) 3 , 11 , 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The FBX dosimeter solution was prepared following the method described by Gupta et al (3) to achieve the following composition: 0.2molnormalm3 ferrous ammonium sulfate, 5.0molnormalm3 benzoic acid, and 0.20molnormalm3 xylenol orange in 40.0molnormalm3 sulfuric acid. All chemicals came from E. Merck (Darmstadt, Germany), except for the xylenol orange, which came from Loba Chemie (Vienna, Austria).…”
Section: Methodsmentioning
confidence: 99%